Interação genótipo ambiente no crescimento ponderal de bovinos da raça Nelore sob enfoque bayesiano - Teixeira, Caio de Souza (2019)
The objective of this study was to evaluate the effects of the genotype by environment interaction (GEI) on the weight growth of Nellore cattle in the Middle- West Region of Brazil. We used standardized weight records at 120 (W120), 210 (W210), 365 (W365) and 450 (W450) days of age from 28,570 Nellore breed animals, progeny of 179 mated breeders with 17,998 matrices from herds of the states of Mato Grosso, Mato Grosso do Sul and Goiás, participating in the Genetic Improvement Program of Nelore - Nelore Breed Brazil of the National Association of Breeders and Researchers (ANCP). For estimation of variance components and subsequent prediction of the genetic values of the animals, for the body weights, were adopted models described for single characteristic (general analysis) and joint that contained fixed effects referring to the contemporary group classes and linear and quadratic effect of the cow's age at calving, as a covariate, in addition to random effects related to direct additive genetic values, maternal permanent environment effects, maternal genetic effects. For W365 and W450, the models did not adopt maternal and maternal genetic effects. Changes in estimates of a posteriori means of the variance components between the models were observed, which influenced the prediction of the genetic values, being these divergent among states, mainly for weaning weight (W120 and W210). The a posteriori coefficients of genetic correlations ranged from 0.41 to 0.97, but were mostly less than 0.80. There were alterations in the ranking of breeders when Spearman correlation coefficients were observed of 0.41 and between Mato Grosso and Mato Grosso do Sul and 0.59 between Goiás and Mato Grosso do Sul for W120 and W365 respectively. It was verified that there is the GEI on the ponderal development of Nellore cattle in the Middle-West Region of Brazil, so this should be considered for the best prediction of the genetic value of the animals, which supports the selection and the genetic progress.